Divorced in a Flash: The Effect of the Administrative Divorce Option on Marital Stability in the Netherlands - Jan Kabátek (Institute of Labor Economics (IZA), 2019)
Administrative divorce is an optional divorce procedure which allows couples to bypass the court system and dissolve their marriages in a streamlined, uncontested process. The lack of court involvement renders the administrative divorce faster and less expensive than the conventional divorce. In this paper, I investigate whether the administrative divorce option affected the stability of marriages in the Netherlands. Leveraging the ban of the procedure in 2009, I show that the divorce risks were 11.6% higher under the legal regime which allowed for administrative divorce. This effect is causal, and it exhibits considerable heterogeneity, being stronger among dual-earner couples, native couples, and couples living in rural regions.
Keywords: J12; J18; K36; 330; marital stability; divorce; administrative divorce; divorce costs